Conformation tuning of simple non-fused electron acceptors via oxygen and sulfur substitutions and its effects on photovoltaics. Issue 2 (14th April 2021) - Yao, Zhenghui; Li, Yaokai; Li, Shuixing; Shi, Minmin; Chen, Hongzheng
Abstract: By altering the number and position of oxygen and sulfur substitutions, four simple non-fused electron acceptors, PTO-4F, PDO-4F, PDS-4F and PTS-4F, were synthesized via feasible two-step reactions. These four acceptors serve as good molecular models to investigate the heteroatom effects on performance of organic solar cells (OSCs) based on their blends with typical polymer donor PBDB-T. The quantity of intramolecular noncovalent bonds, conformation of the molecules and performance of OSCs can be easily adjusted. Gradually increasing oxygen atoms could influence the intramolecular noncovalent (O·S, O·H) interactions, backbone planarity, film morphology, and electrical and photovoltaic properties significantly. When replacing O atoms with S atoms, the torsional angle of the backbone increases from 3.5° to 97° owing to the reduction of O·S attractive coulomb interaction and/or O·H hydrogen bonding interaction. With increasing oxygen atom numbers, the absorption is red-shifted gradually and the energy levels are lifted. As a result, the power conversion efficiency of the device increases from 4.06% (PTS-4F) to 6.81% (PTO-4F). This study provides helpful molecular design guideline for the optimization of simple non-fused acceptors and device performances by finely controlling the weak intramolecular noncovalent interactions and molecular conformations.